2019
DOI: 10.2147/cmar.s188172
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nonspecific immunoglobulin G is effective in preventing and treating cancer in mice</p>

Abstract: BackgroundPrevious accidental findings showed that administration of immunoglobulin G (IgG) in treating autoimmune diseases was able to inhibit cancers that happened to grow in these patients. However, such treatment has not been used to treat cancer patients clinically. The mechanism and optimal dosages of this treatment have not been established. Subsequent animal experiments confirmed this effect, but all previous studies in animal models used human IgG which was heterogeneous to the animal hosts and theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Unexpectedly, control IgG treatment showed similar basement membrane normalization effects as Nintedanib did, compared to control gavage treatment. Recently, syngeneic low dose IgG was shown to counteract cancer progression in melanoma, colon cancer and breast cancer mouse models, inhibiting tumor vessel proliferation and prolonging survival [ 36 ]. Anti-tumor effects of unspecific IgG have also been reported using human IgG in animal models [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, control IgG treatment showed similar basement membrane normalization effects as Nintedanib did, compared to control gavage treatment. Recently, syngeneic low dose IgG was shown to counteract cancer progression in melanoma, colon cancer and breast cancer mouse models, inhibiting tumor vessel proliferation and prolonging survival [ 36 ]. Anti-tumor effects of unspecific IgG have also been reported using human IgG in animal models [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, syngeneic low dose IgG was shown to counteract cancer progression in melanoma, colon cancer and breast cancer mouse models, inhibiting tumor vessel proliferation and prolonging survival [ 36 ]. Anti-tumor effects of unspecific IgG have also been reported using human IgG in animal models [ 36 , 37 ]. In several case reports, cancer patients who received intravenous immunoglobulin (IVIg) therapy e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is recent clinical and pre-clinical data on using immunoglobulins for cancer therapy. The increasing number of pathologies where intravenous immunoglobulins (IVIg) display a beneficial action illustrates their therapeutic relevance [33], [34]. Possible mechanisms of action include the ability of IVIg to modulate macrophage polarization toward M1-like phenotype, characterized by pro-inflammatory activity and inhibition of proliferation of cancer cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…IVIg has been safely employed in the treatment of autoimmune diseases and immunodeficiency. Data from human and animal models have demonstrated that IVIg can inhibit cancer progression as well as prolong survival ( Sobieszczańska et al., 2014 ; Xu et al., 2019 ). A case report of patients with ICI-induced myocarditis showed that treatment with IVIg and statins resulted in rapid recovery from myocarditis without compromising the effectiveness of ICI therapy ( Balanescu et al., 2020 ).…”
Section: Efforts To Uncouple Antitumor Immunity From Inflammation-drimentioning
confidence: 99%